2009
DOI: 10.1016/j.serrev.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Survey and Analysis of Electronic Journal Licenses for Long-Term Access Provisions in Tertiary New Zealand Academic Libraries

Abstract: A survey of New Zealand university and polytechnic libraries indicates what proportions of library ejournal holdings have archival rights or perpetual access clauses. The author then analyzes licenses from three universities for terms, permissions, and other details. The research indicates that less than 20% of the online holdings for most New Zealand educational libraries had a print duplicate, archive, or perpetual access right. Licenses failed to address these access and rights issues in 70% of the cases su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Participants responded to LC principle-based questions using a score scale ranging from -10 to +10. A positive +5 score indicated a 50% adoption of a specific LC principle, while a negative score of -5 implied opposition to the principle up to 50%, following the approach of Rogers [60]. A sample question and the scale are shown in Table 3.…”
Section: Figure 1 Research Methodologymentioning
confidence: 99%
“…Participants responded to LC principle-based questions using a score scale ranging from -10 to +10. A positive +5 score indicated a 50% adoption of a specific LC principle, while a negative score of -5 implied opposition to the principle up to 50%, following the approach of Rogers [60]. A sample question and the scale are shown in Table 3.…”
Section: Figure 1 Research Methodologymentioning
confidence: 99%
“…In comparison, 2007-8 statistics show that ARL libraries spent an average of about $7.5 million for current serials, and ASERL libraries spent an average of about $6 million for these resources. 27 Replies to question 4 show that, in comparison with the previous fiscal cycle, the largest number of libraries (21) have experienced no change in their funds for journal acquisitions (see figure 2). Another 18 of the libraries experienced decreases in funding, and the remaining 9 libraries experienced increases in funding.…”
Section: Respondents' Librariesmentioning
confidence: 99%
“…From November 2006 through January 2007, Rogers surveyed New Zealand university and polytechnic libraries regarding the portion of the libraries' journals with archival rights or perpetual access provisions. 21 He found that, despite the libraries' stewardship commitments, only 30 percent of their licenses explicitly ensured long-term access. Stemper and Barribeau reported similar findings in 2006.…”
Section: (1) Lrtsmentioning
confidence: 99%
“…Rogers examined long-term access provisions in electronic journal license agreements in place for university and polytechnic libraries in New Zealand and determined that even though libraries value perpetual access and archival guarantees, these rights are often missing from negotiated license agreements. 134 Rogers found that licenses failed to address perpetual access or archival rights in 70 percent of the agreements reviewed. Zambare and colleagues also found that the provisions for these rights in license agreements were unacceptable.…”
Section: Ensuring Perpetual Access To Electronic Contentmentioning
confidence: 99%